Rocket and the perfect pumpkin - Stephens, Elle; Hills, Tad (Step into reading., 2020)
Rocket and Bella find the perfect pumpkin, but it rolls away from them and they chase it all the way to Mr. Barker's house, where it makes their friend very happy.